Conflicts Revealing Power, Politics and Identities in a Finnish University Merger - Rossi, Paula; Poutanen, Mikko (Focus Localis ry, 2026)
This empirical study of a university merger in Finland explores the conflicts that emerged among academic staff and seeks to derive lessons for public sector reform in the contexts of public sector organizational change. The theoretical approach of our article focuses on experienced conflicts by drawing on studies of public management and deepens our understanding of managing mergers in higher education. The analysis reveals conflicts related to power, politics, and identity struggles among the staff of the merging organizations. Our findings show that stifling conflict is likely to create horizontal polarization that will find expression elsewhere and jeopardize a successful merger, which is the purpose of the change process. Managing staff expectations becomes an issue of public sector reform also from the perspective of increased expectations levied on universities in terms of local and national economic development and innovation.

Artikkelissa tarkastellaan suomalaisen yliopistofuusion sisäistä konfliktia fuusioituvien yliopistojen henkilöstön näkökulmasta. Yliopistofuusiot ovat merkittäviä julkisen sektorin organisaatiomuutoksia, joissa johtajuus korostuu. Nojaten julkisjohtamisen kirjallisuuteen koetuista konflikteista artikkeli syventää ymmärrystä siitä, miten nimenomaan yliopistofuusion kaltaisessa jännitteisessä organisaation muutostilanteessa organisaatiokonfliktin osapuolet asemoituvat. Analyysi paikantaa vallankäyttöön, politiikkaan ja identiteettikamppailuun liittyviä konflikteja haastatteluaineistosta. Tulokset antavat viitteitä siitä, että ylhäältä alaspäin johdetun muutosprosessin jännitteet voivat purkautua horisontaalisesti fuusioituvassa työyhteisössä. Konfliktipaineiden purkautuminen horisontaalisesti voi herättää negatiivisia tunteita uudessa organisaatiossa, vaikuttaen näin fuusioprosessiinkin. Organisaatiomuutoksen keskeisten toimijoiden on hyvä olla tietoisia näistä konflikteista, niiden jännitteistä, ja niiden mahdollisista purkautumismuodoista. Tämä koskee erityisesti Suomessa yleisiksi tulleita korkeakoulufuusioita.
Keywords: reformit; julkinen sektori; implementointi; konfliktit; yliopistot; public sector reform; public policy; implementation; conflicts; universities; fi=Julkisjohtaminen|en=Public Management|